Stunting was not associated with attention deficit hyperactivity disorder (ADHD) in children 36-59 month in Sedayu Subdistrict - Dwi Nur Rahmawati; Bunga Astria Paramashanti; Rosma Fyki Kamala (Alma Ata University Press, 2017)
Background: Results of Riskesdas in 2013 showed the prevalence of stunting by 37%. Stunting is a growth disorders such as chronic malnutrition will cause linear growth of troubled children. Stunting apart from the impact of the development of IQ, cognitive and motoric sector but also on emotional development. Hyperactivity disorder or ADHD (Attention Deficit Hyperactivity Disorder) is one of the emotional problems in children.Objective: The general objective of this study was to determine the relationship between stunting with attention deficit hyperactivity disorder in children aged 36-59 months in the Sedayu Subdistrict, Bantul District, Yogyakarta in 2017.Methods: This study used a cross-sectional approach. The samples studied amount 185 samples retrieval techniques probability proportional to size (PPS). Variable examined included stunting and hyperactivity disorder.: The prevalence of stunting in this study was 34,2%, meanwhile the prevalence of hyperactivity was 28,8%. Chi-square analysis showed no significant association between stunting with attention deficit hyperactivity disorder (OR=0,98; 95%CI: 0,50-1,91).Conclusion: there was no association between stunting and hyperactivity in young children. KEYWORDS: stunting, hyperactivity, ADHD, children